Toward a comprehensive global electric circuit model: Atmospheric conductivity and its variability in CESM1(WACCM) model simulations. Issue 16 (28th August 2013) - G. Baumgaertner, A. J.; Thayer, J. P.; Neely, R. R.; Lucas, G.
Abstract : [1] As an important step in further modeling and understanding the global electric circuit, the Community Earth System Model (CESM1) has been extended to provide a calculation of conductivity in the troposphere and stratosphere. Conductivity depends on ion mobility and ion concentration, the latter being controlled by a number of ion production and loss processes. This leads to a complex dependency of conductivity on most importantly galactic cosmic ray flux, radon emissions from the Earth's surface, aerosol number concentrations, clouds, and temperature. To cover this variety in parameters for calculating and evaluating conductivity, an Earth system model is extremely useful. Here the extension of CESM1 to calculate conductivity is described, and the results are discussed with a focus on their spatial and temporal variabilities. The results are also compared to balloon and aircraft measurements, and good agreement is found for undisturbed conditions and during a solar proton event. The conductivity model implementation is a significant improvement to previous studies because of the high‐quality, high‐resolution model data input. Notably, the aerosol representation provided by off‐line calculations of tropospheric and stratospheric aerosol using the Community Aerosol and Radiation Model for Atmospheres as part of CESM1(WACCM) (Whole Atmosphere Community Climate Model) provides a realistic computation of the impact of the background aerosol distribution for the first time. In addition to the novel high‐resolution information on conductivity, it is found that an intra‐annual cycle exists in the total global resistance, varying between 220 and 245 Ω. The model shows that this cycle is driven equally by seasonal aerosol and cloud variations. Key Points: Electrical conductivity calculation using an Earth System Model Unprecedented picture of conductivity in the troposphere/stratosphere Clouds and aerosols induce intra‐annual cycle in global resistance